A review of literature on parenting styles, parental competence and emotional intelligence among college students - Joseph, Okoye Chukwuebuka; Hasbullah @ Abdullah, Muslihah; Arshat, Zarinah (Institute of Medico-legal Publications, 2021)
Parenting styles and competence predict many aspects of the children’s well-being. Studies indicate that parents present the first learning environment for their children before joining schools, and that the impacts they have to their children may influence their children up to college level. Although many studies have been conducted on the impacts of parenting style and parental competence on emotional intelligence, majority of these are mainly in the context of Western or Asian countries and little, or none in the context Nigeria, particularly, in urban area of Anambra State. Therefore, the general objective of the study is to conceptualize the relationships of parenting style and parental competence on emotional intelligence of college students in urban area of Anambra state, Nigeria.